Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning. - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
Oligodendrocytes produce myelin for rapid transmission and saltatory conduction of action potentials in the vertebrate central nervous system. Activation of the myelination program requires several transcription factors including Sox10, Olig2, and Nkx2.2. Functional interactions among them are poorly understood and important components of the regulatory network are still unknown. Here, we identify Nfat proteins as Sox10 targets and regulators of oligodendroglial differentiation in rodents and humans. Overall levels and nuclear fraction increase during differentiation. Inhibition of Nfat activity impedes oligodendrocyte differentiation in vitro and in vivo. On a molecular level, Nfat proteins cooperate with Sox10 to relieve reciprocal repression of Olig2 and Nkx2.2 as precondition for oligodendroglial differentiation and myelination. As Nfat activity depends on calcium-dependent activation of calcineurin signaling, regulatory network and oligodendroglial differentiation become sensitive to calcium signals. NFAT proteins are also detected in human oligodendrocytes, downregulated in active multiple sclerosis lesions and thus likely relevant in demyelinating disease.
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.nfatca

Publisher Correction: Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
The originally published version of this Article omitted Tanja Kuhlmann and Michael Wegner as jointly supervising authors. This has now been corrected in both the PDF and HTML versions of the Article.
EVALuna2:35744

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782